In-Plane Mixed-Mode Brittle Fracture Assessment of Harsin Marble Using HCSP Specimen (Fracture and Structural Integrity, 2024)
The primary objective of this manuscript is studying the effect of T-stress term (T) on the crack propagation angle (CPA) and fracture toughness of in-plane mixed mode loading by utilizing a generalized form of minimum strain energy density (SED) criterion. The generalized criterion considers the influence of the first non-singular term of the Williams stress field as well as the conventional stress intensity factors (SIFs). A specimen known as a holed-cracked square plate (HCSP) composed of white Harsin marble is used for a wide range of in-plane mixed-mode fracture studies. HCSP is a square plate containing two cracks that are placed along each other in the circumference of a hole at the center of the specimen. The experimental results from mixed-mode fracture test by using proposed geometry are then compared with the results obtained theoretically from the conventional and generalized form of SED. It is demonstrated that the generalized criterion which includes the T, is substantially in agreement with the experimentally observed in-plane mixed-mode fracture results when compared to the SED criterion.
Keywords: Mix mode loading; Brittle fracture; Strain Energy; T-stress